Simulation of power supplies used for nonlinear electrical discharges - Lungu, Cristian Victor; Hnatiuc, Bogdan (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This work will present an analysis of the functionality of power supplies producing laboratory controlled electrical discharges using pulsed variation of voltage. The analysis is done on simulated electrical parameters using PROTEUS ISIS software. Furthermore in this paper there will also be presented a simulation of plasma discharge used with power supplies in order to assesstheparameters in functionality of these power supplies.